Comparison of fractional neodymium-doped yttrium aluminum garnet (Nd:YAG) 1064-nm picosecond laser and fractional 1550-nm erbium fiber laser in facial acne scar treatment - Pamela Chayavichitsilp (2020)
© 2019, Springer-Verlag London Ltd., part of Springer Nature. To compare the safety and efficacy of fractional neodymium-doped yttrium aluminum garnet (Nd:YAG) 1064-nm picosecond laser and fractional 1550-nm erbium fiber laser in acne scar treatment and to assess the adverse effects and complications of the two devices. Thirty patients with cosmetically similar acne scars on both sides of the faces were enrolled and treated four times at 4-week intervals. Each side of the face was treated with either fractional 1064-nm Nd:YAG picosecond laser or fractional 1550-nm erbium fiber laser. Efficacy was evaluated using digital photography taken at baseline and 5 months by a blinded dermatologist using the ECCA grading scale (échelle d’évaluation clinique des cicatrices d’acné). Patient overall satisfaction and self-rated improvement scores were recorded at baseline and 5 months. Adverse effects were recorded at every visit. Twenty-seven patients completed the study. Both devices demonstrated significant median ECCA score improvement from baseline (P < 0.001). However, there was no significant difference between the two in terms of median ECCA score improvement, patients’ perception of scar improvement, and overall satisfaction. Considering the adverse effects, more pinpoint bleeding was significantly observed with the picosecond laser (P = 0.002), whereas more pain was noted with the erbium laser (P < 0.001). Both fractional 1064-nm Nd:YAG picosecond laser and fractional 1550-nm erbium fiber laser are safe and effective in the treatment of acne scars. Costs should be taken into consideration when deciding on which device to use to maximize treatment outcomes.